The role of local authority in governing Muslim friendly sport facilities - Ibrahim, Muhammad Irhammudin; Zawawi, Majdah; Ramli, Noriah (Kulliyyah of Languages and Management (KLM), International Islamic University Malaysia (IIUM), 2016)
The needs of the Muslim tourist vary form one type to another, but all tourists need some form of accommodation such as Muslim friendly activities. However they are very few Muslim friendly tourism activities but due to inadequate facilities and attractions that cause very little substances for travel agency to promote Muslim friendly tourism. Current situations indicates that they are no clear guidelines and regulations on how to manage an Islamic and Sharia-compliance sport facilities for the local authority and private company to follow and control. In response to this scenario, this paper aims to provide a greater understanding of Muslim friendly sport facility concept by scrutinizing the Sharia principles framework for sport alongside with fatwas that are already produced to guide Muslim in sport. Besides that, the study also collaborated with the selected local authority in developing the guidelines and procedure in governing and managing the concept of Muslim friendly sport facility that follow the Sharia guidelines. Therefore, there are needs to study and discuss in depth on the issue of the role of the local authority in governing Muslim friendly sport facility in order for Malaysia as a Halal hub for Muslim friendly tourisms that can cater all the needs for the tourist which include providing a decent and sharia compliant sport facility.